2021
DOI: 10.1042/bsr20210491
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spice and herb as phyto-derived selective modulators of human retinaldehyde dehydrogenases using a simple in vitro method

Abstract: Selective modulation of retinaldehyde dehydrogenases (RALDHs) – the main aldehyde dehydrogenase (ALDH) enzymes converting retinal into retinoic acid (RA), is very important not only in the RA signaling pathway but also for the potential regulatory effects on RALDH isozyme-specific processes and RALDH-related cancers. However, very few selective modulators for RALDHs have been identified, partly due to variable overexpression protocols of RALDHs and insensitive activity assay that needs to be addressed. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…RALDHs were assigned to convert retinaldehyde to retinoic acid (RA), acting as the dominant mechanism in RA signaling pathways and relevant cancers. The current study indicated that ethanol extracts of P. anisum selectively and intensively inhibited RALDH3 expression, while it did not modulate RALDH1 and RALDH2, highlighting the selectivity of that in the regulation of RALDHs and the RA-governed metabolic process [ 145 ]. On the other hand, studies on P. anisum ingredients found that abundant bergapten ( 256 ), iso-pimpinellin ( 274 ), and methoxsalen ( 275 ) were inhibitors of CYP-1A2, which are involved in drug metabolism and carcinogenic bioactivity [ 70 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…RALDHs were assigned to convert retinaldehyde to retinoic acid (RA), acting as the dominant mechanism in RA signaling pathways and relevant cancers. The current study indicated that ethanol extracts of P. anisum selectively and intensively inhibited RALDH3 expression, while it did not modulate RALDH1 and RALDH2, highlighting the selectivity of that in the regulation of RALDHs and the RA-governed metabolic process [ 145 ]. On the other hand, studies on P. anisum ingredients found that abundant bergapten ( 256 ), iso-pimpinellin ( 274 ), and methoxsalen ( 275 ) were inhibitors of CYP-1A2, which are involved in drug metabolism and carcinogenic bioactivity [ 70 ].…”
Section: Pharmacologymentioning
confidence: 99%
“…Notably, the terpenoid citral (3,7-dimethyl-2,6-octadien-1-al), a component of essential oils obtained from several plants, which is used as a food additive and fragrance, inhibits human lens ALDH1A1 at low IC50 values of the micromolar range [59]. Spice and herb extracts have shown a wealth in modulatory activities of ALDH family members ALDH1A1, ALDH1A2, ALDH1A3 and ALDH2; even though it may be possible that extracts contain selective modulators, certain extracts manifested general effects, with sage and thyme extracts indicating the potential for complete suppression of the enzymatic activity of all four proteins tested [153].…”
Section: Inhibition Of Aldh As a Potential Therapeutic Approachmentioning
confidence: 99%
“…Bui et al in their interesting paper [ 1 ] focus their attention mainly on retinaldehyde dehydrogenases (RALDHs), which are enzymes converting retinal into retinoic acid (RA). The authors emphasized the need for the search for the compounds having an influence on the activity of these enzymes because of their potential use in cancer therapy.…”
Section: Commentarymentioning
confidence: 99%